Comparative morphology and anatomy of seeds of some Aethionema W.T. Aiton (Brassicaceae) taxa from Turkey (Bangladesh Journal of Plant Taxonomy, 2019)
Seed morphology and anatomy are taxonomically significant in Brassicaceae. The seed structures of Aethionema from Turkey, which include 12 taxa (Aethionema syriacum, A. froedinii, A. arabicum, A. eunomioides, A. fimbriatum, A. speciosum subsp. speciosum, A. speciosum subsp. compactum, A. saxatile, A. oppositifolium, A. iberideum, A. armenum, A. grandiflorum) were studied for knowing seed morphological and anatomical features with one-way analysis of variance, cluster analysis and principal component analysis. Seed size, shape and color were examined with stereomicroscopy.The surface patterns of seed were observed using Scanning Electron Microscopy (SEM). In addition, structure, and thicknesses of testa and endosperm were investigated anatomically. Thickness of testa and endosperm were of major significance to illustrate interspecific relations among the examined taxa.